Use of Fluoroquinolones or Sulfamethoxazole-Trimethoprim Compared to Β-Lactams for Oral Step-Down Therapy in Hospitalized Patients With Uncomplicated Enterobacterales Bacteremia. Issue 3 (March 2023) - Mack, Tyler; Hiles, Jon J.; Wrin, Justin; Desai, Armisha
Background: Antibiotic therapy for uncomplicated Enterobacterales bacteremia from a urinary source has traditionally consisted of fluoroquinolones (FQs) and sulfamethoxazole-trimethoprim (SXT). However, adverse events associated with FQs and emerging antimicrobial resistance have led to alternative agents, specifically oral Β-lactams (OBLs), being utilized despite concern of subtherapeutic serum concentrations related to their low relative bioavailability. Objective: To compare efficacy of antibiotic therapies with bioavailability differences in patients with uncomplicated bacteremia from a urinary source. Methods: This was a retrospective study comparing clinical efficacy in hospitalized adult patients receiving OBL or FQ/SXT. Patients were required to receive at least 48 hours of appropriate intravenous antibiotic therapy and at least one dose of oral therapy. The primary outcome was all-cause hospital readmission within 30 days of discharge. Secondary outcomes included readmission with recurrent infectious etiology and readmission due to Clostridioides difficile infection. Results: Of 210 eligible patients, 91 received FQ/SXT and 119 received OBL. There was no difference between the groups in all-cause hospital readmission (FQ/SXT: 16.5%; OBL: 14.3%) ( P = 0.660 [95% confidence interval, CI = −0.076, 0.120]) or readmission with recurrent bacteremia (FQ/SXT: 0%; OBL: 3.4%) ( P = 0.135). There was a significant difference in repeat hospital admission with recurrent urinary tract infection (UTI) (FQ/SXT: 0%, OBL: 5.0%) ( P = 0.037). Conclusion and Relevance: OBLs appear to be non-inferior to FQ/SXT in the rate of all-cause hospital readmission within 30 days. However, OBLs may be associated with increased readmissions with recurrent UTI.